(untitled) (American Journal of Islam and Society, 2017)
January 2002 saw the launch of several interfaith initiatives from the office of the Archbishop of Canterbury, the spiritual leader of the worldwide Anglican Communion. Of these, the Building Bridges Seminar has sustained itself the most vigorously and has borne the most fruit. Founded out of the sense of urgency following the events of September 11, 2001, and now having met sixteen times, the seminar has been described from its inception as an exercise in “appreciative conversation” made possible by “listening with openness and mutual respect” and characterized by “courage, grace, imagination and sensitivity in addressing and retreating from painful issues.” 1 Presented below is a brief description of its history, methodology, and impact.